Everything, everything - Yoon, Nicola (London : Corgi Books, 2015)
"The story of a teenage girl who's literally allergic to the outside world. When a new family moves in next door, she begins a complicated romance that challenges everything she's ever known. The narrative unfolds via vignettes, diary entries, texts, charts, lists, illustrations, and more"--Provided by publisher.
Kirkus Starred
Publisher's Weekly
School Library Journal starred
Booklist, September 2015
Bulletin (Center for Children's books), December 2015
Horn Book, November 2015
Keywords: Allergy -- Juvenile fiction; Friendship -- Juvenile fiction; Racially mixed people -- Juvenile fiction; Allergy -- Fiction; Friendship -- Fiction; Racially mixed people -- Fiction; Allergy -- Fiction; Friendship -- Fiction; Racially mixed people -- Fiction; Romance fiction